2014
DOI: 10.1007/s00405-014-3003-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in electrogustometry thresholds, tongue tip vascularization, density and form of the fungiform papillae in smokers

Abstract: The objective of this study was to evaluate differences in gustatory function in smokers of both sexes and identify any differences in the shape, density and vascularisation of the fungiform papillae (fPap) of smokers' tongue. Additional aim was to investigate any relation between the age, pack years and differences in shape, density, vascularization of fPap and sex. In 166 smokers (81 males, 85 females, age range 20-80 years), divided in age groups, electrogustometry (EGM) thresholds at the chorda tympani are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 14 publications
5
30
0
1
Order By: Relevance
“…These results may help to enhance the understanding of these relationships in populations with elevated diet-related health risks.Nutrients 2019, 11, 3052 2 of 12 showed that T1D was associated with a reduction in gustatory function [3,5,7], with impairments mostly found with respect to the sweet taste perception in comparison to other taste modalities [10,11]. In addition, Pavlidis and colleagues [12] found impairments in the density and morphology of the fungiform papillae (FP) among patients with diabetes, which are the gustatory anatomical structures containing taste buds.Data in the literature suggest that the inherited ability to perceive bitter thiourea compounds, such as 6-n-propylthiouracil (PROP), may be a surrogate measure of taste perception and a marker for increased health risk. Variation in taste responsiveness to PROP has been linked to various health disorders, including obesity [13] and diabetes [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results may help to enhance the understanding of these relationships in populations with elevated diet-related health risks.Nutrients 2019, 11, 3052 2 of 12 showed that T1D was associated with a reduction in gustatory function [3,5,7], with impairments mostly found with respect to the sweet taste perception in comparison to other taste modalities [10,11]. In addition, Pavlidis and colleagues [12] found impairments in the density and morphology of the fungiform papillae (FP) among patients with diabetes, which are the gustatory anatomical structures containing taste buds.Data in the literature suggest that the inherited ability to perceive bitter thiourea compounds, such as 6-n-propylthiouracil (PROP), may be a surrogate measure of taste perception and a marker for increased health risk. Variation in taste responsiveness to PROP has been linked to various health disorders, including obesity [13] and diabetes [14].…”
mentioning
confidence: 99%
“…Nutrients 2019, 11, 3052 2 of 12 showed that T1D was associated with a reduction in gustatory function [3,5,7], with impairments mostly found with respect to the sweet taste perception in comparison to other taste modalities [10,11]. In addition, Pavlidis and colleagues [12] found impairments in the density and morphology of the fungiform papillae (FP) among patients with diabetes, which are the gustatory anatomical structures containing taste buds.…”
mentioning
confidence: 99%
“…Furthermore, a type of vasculitis called Thromboangiitis (TAO) (also known as Buerger's disease), is heavily associated with smoking and vasculitis [9] . Smokers in general also have an overall decreased tongue vascularization [19] . These facts could suggest that smoking increases the risk of thrombosis in the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…42 Nevertheless, higher taste detection thresholds have been observed in smokers 43 and may be related to lower fungiform papillae density and functionality 44,45 and to reduced gene expression in several sub-types of TAS2R receptors (including TAS2R38). 46 The present study revealed an increase in taste intensity for both NaCl and PROP measured at week 2 of a smoking abstinence trial, consistent with a short-term recovery in taste function.…”
Section: Discussionmentioning
confidence: 99%